Vitiligo impact scale: An instrument to assess the psychosocial burden of vitiligo - Krishna, Gaurang; Ramam, M; Mehta, Manju; Sreenivas, V; Sharma, Vinod; Khandpur, Sujay (Indian journal of dermatology, venereology, and leprology, 2013)
Background : Vitiligo is a disease that significantly impairs quality of life. Previous studies have shown that vitiligo has an impact that may not correlate with the size and extent of depigmentation, indicating a need for an independent measure of the psychosocial burden. Aims : To develop a rating scale to assess the psychosocial impact of vitiligo. Methods : The study was undertaken in three broad phases: item generation, pre- and pilot testing, and test administration. Items were generated largely from a qualitative study using semi-structured interviews of patients. Face and content validity were assessed through pre- and pilot testing in 80 patients and the final version was administered to 100 patients who also received the Dermatology Life Quality Index (DLQI) and the Skindex-16. Each patient also underwent a physician global assessment (PGA) of the impact of vitiligo. Test-retest reliability was assessed in 20 patients. Results: Of 72 items initially generated for the scale, 27 were retained in the final version. Subjects were able to comprehend the items and took about 5-7 min to complete the instrument. The scale was internally consistent (Cronbach′s α = 0.85). Scores on the scale correlated moderately well with the DLQI and the Skindex (Spearman rank correlation: 0.51 and 0.65, respectively). The scale was able to discriminate between patients having mild and those having moderate and severe impact as assessed by PGA. The test-retest reliability coefficient (Spearman rank correlation) was 0.80. Conclusion: The Vitiligo Impact Scale appears to be a valid measure of the psychosocial impact of vitiligo and this instrument may be useful both in the clinic and in clinical trials.